Comparison of the therapeutic role of garlic extract and verapamil against gentamicin-induced nephrotoxicity in rats (Journal of Pharmaceutical Negative Results, 2022)
Background: The aminoglycoside group, especially gentamicin, is the critical antibiotic in severe Gram-negative bacterial infections through its significant risk of nephrotoxicity. There are many protective factors for the kidneys, including blocking the flow of calcium to the damaged cells of the kidneys and reducing renal blood flow through the drug verapamil, In the same regard, garlic has been proven to be an antioxidant, a natural plant remedy for kidney protection.Aim of the study: Knowledge of enzymatic changes in the kidney due to gentamicin treatment and the role of garlic alcohol extract and verapamil in improving these changes.Methods and materials: 40 rats (3 to 6 months old) were brought up at normal temperature and divided into four equal groups, each group included 10 rats, including the negative control group, which were given orally 0.9% physiological salt solution, and the second group, the positive control (treated with G) 80 mg/kg by intraperitoneal injection, and the third group was given (G) 80 mg/kg intraperitoneally with (V) 3 mg/kg orally, And the fourth group had been injected with (G) 80 mg/kg intraperitoneally with (GAE) 20 mg/kg orally. The study included the evaluation of some biochemical blood parameters, including: levels of creatinine, urea, total protein, sodium, potassium, malondialdehyde (MDA), glutathione (GSH), and catalase (CAT). Above these criteria were the study of the median lethal dose (LD50).Results: The statistical analysis of the results showed: - The results of the current study, through the results of the statistical analysis, showed a significant increase (P<0.05) in the effectiveness of the levels of urea, creatinine, sodium, Dimalone Dehyde (MDA) when comparing the positive control group treated with (G) at a concentration of 80 mg/ In contrast, the levels of total protein, potassium, glutathione (GSH), catalase (CAT) significantly decreased (P<0.05) in the positive control group when compared with the other experimental groups.Conclusion: Garlic alcoholic extract and verapamil are highly effective in protecting blood biochemical parameters from gentamicin-induced nephrotoxicity.